Clinical enigma: A rare case of clear cell odontogenic carcinoma - Cheshta Walia; Rudra Prasad Chatterjee; Sanchita Kundu; Sudip Roy (Wolters Kluwer Medknow Publications, 2015)
Clear cell odontogenic carcinoma is a rare, aggressive neoplasm of the jaw with only 74 reported cases. It occurs predominantly in the mandibular anterior region during fifth to seventh decades of life. Clinically it manifests as intra-bony swelling with a variable degree of pain. Microscopically, it reveals nests of cells with clear cytoplasm in connective tissue stroma arranged in different patterns. It is often misdiagnosed due to the rarity of lesion and confusing histopathology. Immunohistochemical staining plays an intricate role to uncertain the native of the clear cell to reach a confirmative diagnosis. The article aims to highlight the clinicopathologic features of clear cell odontogenic carcinoma in a middle-aged man with special emphasis on its differential diagnosis.